Exposure to O3 during pregnancy and offspring asthma induced by OVA: Sensitive window identification. (1st February 2021) - Liu, Xinai; Fu, Lingling; Yang, Xiwei; Wang, Zhiping
Abstract: Background: Evidence proved that gestational ozone (O3 ) exposure can increase the risk of neonatal adverse respiratory outcomes, but offspring asthma is unclear. Objective: This study aimed to investigate whether gestational O3 exposure could exacerbate offspring asthma, and to research the differences in effects of O3 exposure at different gestational periods on offspring asthma. Methods: The pregnant ICR mice were randomly grouped and were administered O3 (air as control) at gestational day (GD) 1–6, 7–12, and 13–18, respectively. The pups aged 2–4 weeks were treated with ovalbumin (OVA) to establish a model of early life asthma. Asthma characteristics such as pulmonary inflammation, goblet cell proliferation, airway remodeling, OVA-specific immunoglobulin (Ig) E secretion and cytokines were examined. Results: OVA sensitization and challenge successfully induced asthma in offspring. Compared with the air control, pulmonary inflammation infiltration, mucous secretion, the concentration of OVA-specific IgE, the level of tumor necrosis factor (TNF)-α, and T helper (Th) 2-skewed response were significantly exacerbated when O3 exposure at GD13-18 following inhaling OVA, while pulmonary inflammatory infiltration, mucus secretion, and Th2-skewed response were not significantly changed when O3 exposure at both GD1-6 and GD7-12. What's more, the above indicators in asthmatic offspring due to O3 exposure at GD13-18 were more severe than at GD1-6 and GD7-12. Interestingly, the signs of asthma only appeared in the offspring after OVA inhalation. When offspring were not treated with OVA, the prenatal O3 exposure alone did not lead to asthmatic reactions in offspring. In addition, O3 exposure at GD13-18 markedly increased the number of neutrophils and macrophages in Bronchoalveolar Lavage Fluid (BALF) of asthmatic offspring, and significantly exacerbated Th2 immune imbalance in asthmatic offspring, but had no effect on Th17 immune imbalance. Conclusion: Exposure to O3 during pregnancy aggravated asthma in offspring, in which the third trimester is the most sensitive window. Graphical abstract: Image 1 Highlights: Exposure to O3 during pregnancy exacerbated OVA-induced asthma in offspring. The third trimester was the sensitive window for O3 transgenerational toxicity. Neutrophil and macrophage infiltration was the main feature in offspring asthma. Th1/Th2 immune imbalance in asthmatic offspring was exacerbated. The model of offspring asthma in early life was established and applied. Abstract : Capsule: Exposure to O3 during pregnancy aggravated OVA-induced asthma in offspring, in which the third trimester is the most sensitive window.